Basic causes of death and survivorship according to race/color and sex in Bahia, period 2010-2020 (Research, Society and Development, 2022)
Racial differences are associated with social inequalities and condition people's way of life, and can determine the health and illness of a given group. The purpose of this research was to analyze mortality by underlying cause of death, survivorship and differentials by race/color and sex in Bahia. This is an epidemiological, quantitative study, with secondary data from the SIM. The association between the variables “basic cause of death” and “race/color” was evaluated using the chi-square test, the relationships between all categories of both variables were studied in a simple correspondence analysis, and if a survival analysis to compare the curves. The results reveal that women have a better survival time than men. There is a statistically significant association between cause of death and race/color (p